Antithrombotic Therapy and the Nearest Forecast of Pulmonary Embolism in Rutine Clinical Practice (Data of the Regional Vascular Center of the Ryazan Region) - N. N. Nikulina; Yu. V. Terekhovskaya; S. S. Yakushin (Рациональная фармакотерапия в кардиологии)
Aim. To perform the analysis of antithrombotic therapy and immediate prognosis in patients with pulmonary embolism (PE) in routine clinical practice.Materials and methods. During 13 months of follow-up (2018-2019) within the framework of the Russian SIRENA registry, the study included patients (n=103) with verified PE who were hospitalized at the regional vascular center. Main results. Thrombolytic therapy was performed in 63 patients (61.2% of the sample), of which 48 (76.2%) had no indications. In these cases, the most common reason for performance was the results of the PESI score (n=17) and/or a significant amount of damage to the pulmonary artery (n=10) and/or severe shortness of breath (n=3) and/or the presence of a thrombus in the right parts of the heart or deep veins of the lower extremities (n=2), in addition, in a number of medical records, the cause is indicated as “for health reasons” (n=6) or there were no data (n=10). Patients who underwent thrombolysis had a larger volume of pulmonary lesions, more pronounced signs of respiratory failure and overload of the right heart, as well as a shorter duration of clinical manifestations. Anticoagulant therapy was used in 94.2% of cases, of which 90.3% of patients used parenteral forms at the start, then direct oral anticoagulants were mainly used, the frequency of warfarin prescription was only 5.8% of cases. Bleeding was registered in 19.4% of patients (significant – in 11.7%). PE recurrence after diagnosis and initiation of therapy was observed in 4 cases (3.9%). Hospital mortality was 9.7%. Predictors of poor prognosis were hospitalization with a different diagnosis (risk ratio [RR] 16.2; p=0.001), advanced age (RR 10.1; p=0.028), unstable hemodynamics (RR 7.6; p=0.002), chronic kidney disease C3- 5 (RR 5.6; p=0.03), history of stroke (RR 5.3; p=0.016) and chronic heart failure (RR 3.9; p=0.035).Conclusion. In modern clinical practice, the indications for thrombolysis often differ from those recommended, which leads to an increase in the number of bleeding and leveling of the positive effect on the prognosis. Factors such as advanced age, chronic heart failure and atrial fibrillation, stroke, chronic kidney disease, hemodynamic instability, hospitalizations with a different primary diagnosis, and the need for oxygen therapy increase the risk of early mortality.